Theoretical study of steady-state characteristics of natural circulation system. (November 2020) - Song, Gongle; Wu, Di; Sun, Rulei; Liang, Yu; Zhang, Dalin; Deng, Jian; Su, Guanghui; Tian, Wenxi; Qiu, Suizheng
Highlights: The conservation equations are established for the natural circulation system. A set of constitutive models are obtained to solve thermal hydraulic parameters. The modular modeling is universal for systems with different structures. Mass flow increases with heat flux increasing and inlet subcooling decreasing. The influence of phase change depends on the structural characteristics. Abstract: In this paper, the conservation equations of mass, momentum and energy are established for the natural circulation system. A complete set of constitutive models for solving the steady-state thermal hydraulic parameters are obtained including heat conduction, condenser, pipe, pressurizer, system flow and other auxiliary modules. For calculating natural circulation systems with different structures conveniently, the modular modeling method is adopted. By comparing with the data of different experiments, it proves that modular modeling is universal for systems with different structures, and the correctness of the process of model establishment and model solution is also proved. It is found that the mass flow would increase with the increase of heat flux and the decrease of inlet subcooling of test section. The influence of phase change on the mass flow depended on the structural characteristics of the system. The appearance of two-phase not only increases the driving force of natural circulation system, but also increases the flow resistance. When the increase of driving force is dominant, the appearance of two-phase will further increase the mass flow. Otherwise, the two-phase flow will hinder the increase of mass flow and may even cause its decrease. For the structural design of natural circulation system, the introduction of large form resistance should be avoided as far as possible so as to avoid the establishment of natural circulation process hindered by two-phase flow. The steady-state model of natural circulation system established in this paper has laid a good foundation for the following transient studies and is of great significance.